ANALYSIS OF FLOUTING OF CONVERSATIONAL MAXIMS BY CHARACTERS IN THE HELP MOVIE - Hamidah, Nurul; Arifin, M. Bahri; Ariani, Setya (Ilmu Budaya: Jurnal Bahasa, Sastra, Seni, dan Budaya, 2022)
ABSTRACT This study focused on analyzing  flouting of maxim that was performed by characters and the reasons for characters flouting maxims in The Help movie. This study used a qualitative content analysis. The data source was from The Help movie’s script. The data were in the form of dialogues and utterances among characters that contained of flouting maxims. Through the analysis process, the researcher found 32 data containing of all flouting of maxim types: flouting of maxim of quantity, flouting maxim of quality, flouting of maxim of relevance, and flouting of maxim of manner. In addition, the characters flouted the maxims due to several reasons such as competitive, convivial, collaborative, and conflictive. Maxim of quality became the most frequent flouted type and mostly came together with conflictive through making sarcastic utterances. The characters gave sarcastic utterances because the interlocutors kept talking about the speaker’s dislike topic, such as getting marriage and downgrading the job.Key words: Cooperative Principle, Conversational Maxims, Flouting of Maxims ABSTRAKFokus penelitian ini adalah untuk menganalisa jenis penyimpangan maksim yang dilakukan oleh karatkter dan alasan mengapa mereka menyimpang maksim di film The Help. Penelitian ini menggunakan metode penelitian analisis kualitatif pada konten. Sumber data adalah dari naskah film The Help dan data dalam bentuk dialog dan ujaran antara karakter yang berisi penyimpangan terhadap maksim. Setelah menganalisa data, peneliti menemukan 32 data yang menunjukkan semua jenis maksim telah disimpangkan di film The Help, yaitu maksim kuantitas, maksim kualitas, maksim relevansi, dan maksim cara. Selain itu, karakter menyimpang maksim karna beberapa alasan, yaitu kompetitif, konvivial, kolaboratif, dan konfliktif. Maksim kualitas menjadi tipe yang paling sering disimpang dan hampir semua menggunakan konfliktif sebagai alasan dengan membuat ujaran sarkastik. Ujaran sarkastik dibuat untuk menyinggung lawan bicara karena mereka terus membahas topik yang tidak disukai oleh penutur, seperti menyuruh untuk cepat menikah dan merendahkan pekerjaan.Kata kunci: Prinsip kooperatif, maksim konvensional, pinyampangan maksim.